Abnormal hearing patterns are not associated with endothelium-dependent vasodilation and carotid intima–media thickness: The Framingham Heart Study. (December 2021) - Tyagi, Sudhi; Friedland, David R; Rein, Lisa; Tarima, Sergey S; Mueller, Christopher; Benjamin, Emelia J; Vasan, Ramachandran S; Hamburg, Naomi M; Widlansky, Michael E
Introduction: Prior data suggest associations between hearing loss, cardiovascular (CV) risk factors, and CV disease. Whether specific hearing loss patterns, including a strial pattern associated with inner ear vascular disease, are associated with systemic endothelial dysfunction and carotid intima–media thickness (IMT) remains unclear. Methods: We evaluated participants without prevalent CVD in the Framingham Offspring Study who underwent formal audiogram testing and brachial and carotid artery ultrasounds. Audiograms were categorized as normal or as belonging to one of four abnormal patterns: cochlear-conductive, low-sloping, sensorineural, or strial. Endothelial function as measured by brachial artery flow-mediated dilation (FMDmm and FMD%). Internal and common intima–media thicknesses (icIMT and ccIMT, respectively) were compared between audiogram patterns. Results: We studied 1672 participants (mean age 59 years, 57.6% women). The prevalence of each hearing pattern was as follows: 43.7% normal; 20.3% cochlear-conductive; 20.3% sensorineural; 7.7% low-sloping; and 8.0% strial. Strial pattern hearing loss was nearly twice as prevalent ( p = 0.001) in those in the highest quartile of ccIMT and nearly 50% higher in those in the highest icIMT quartile ( p = 0.04). There were no statistically significant differences between the prevalence of the strial pattern comparing the lowest quartiles of FMDmm and FMD% with the upper three quartiles. Age- and sex-adjusted linear regression models did not show significant associations between the vascular measures and hearing patterns. Conclusion: Abnormal hearing patterns were not significantly associated with impaired brachial FMD and increased carotid IMT after adjusting for age and sex effects, which may reflect age and sex-related distributional differences based on hearing loss pattern.